A RARE CASE REPORT ON TUBULAR APOCRINE ADENOMA - Kaushal, Neetika; Pandey, Priyanka (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Tubular apocrine adenoma, the apocrine variant of papillary tubulopapillary hidradenoma, is a rare well-circumscribed, intradermal benign tumor, with tubular structures showing apocrine differentiation. It usually presents as a slow-growing well-circumscribed nodule. The most common site of involvement is the scalp, although it has also been reported to occur at other sites like face, neck, axilla, trunk, upper and lower extremities. The present study describes a case of 76-year-old female who presented with swelling on back. An excisional biopsy was performed which on histopathological examination shows multiple irregular-shaped tubular structures lined by two layers of epithelial cells focally. On histopathology, the case was diagnosed as tubular apocrine adenoma.